Using allele-specific markers of genes Ppd and Vrn for the analysis of precocity wheat somaclonal lines (Experimental biology, 2016)
A molecular biological analysis of wheat precocity somaclonal lines and initial cultivars to the presence of a combination of gene alleles Ppd (Photoperiod) and Vrn (Vernalization), responsible for reaction of plants to photoperiod and vernalization, indicating the terms of earing that control growth and development phase of soft wheat. Differ the precocity lines cv. Otan of R9 generation from the initial cultivar by the presence of allele gene Vrn-A1a and absence of allele gene Vrn-B1 was established. Identity between the initial variety and Cselinnaya 3S not dumped precocity line by dominant allele gene Vrn-A1a and difference by the dominant allele gene Vrn-B1 were show. Thus, in Cselinnaya 3S not dumped precocity line the dominant allele gene Vrn-B1 was revealed, which is absent in the initial cultivar.
Keywords: somaclonal lines; wheat; Ppd and Vrn genes; precocity.